Non-equilibrium simulation of energy relaxation for earth reentry utilizing a collisional-radiative model. (April 2022) - Du, Yao-Wen; Sun, Su-Rong; Tan, Mei-Jing; Zhou, Yu; Chen, Xuan; Meng, Xian; Wang, Hai-Xing
Abstract: A high-temperature air collisional-radiative model considering both vibrational and electronic excited states is established to investigate the plasma characteristics along the stagnation-line in the post-shock flow by coupling with the one-dimensional flow model. The results obtained by the model are in reasonable agreement with the experimental data and previous calculation results. The evolutions of different temperatures and energy relaxation processes are analyzed in detail for the height of 76.42 km and Mach number of 40.58. The vibrational and electronic excited modes play a critical role on the energy transfer. The vibrational excitation processes under heavy-particle impact can transfer the translational energy to the vibrational mode, then to the electrons by the vibrational de-excitation processes. The excitation of atoms by heavy-particle impact can gain energy from the translational mode, and the de-excitation processes of high-lying excited states under electron impact result in the energy transfer to electrons. The elastic collisions also play a role on the direct transfer from translational energy to electrons. The calculations are performed for a wide range of flight altitudes and Mach numbers to investigate the thermochemical state and energy relaxation. By comparing the energy transfer processes under different altitudes and Mach numbers, it is found that the energy transfer is dominated by vibrational processes for the low-Height low-Mach condition, and the contribution of electronic excited mode is negligible. The division of thermochemical state and chemical reactions in the Height-Mach number diagram is obtained, which provides the basis for the selection of thermochemical model required for atmospheric reentry calculation. Highlights: A CR model coupled with 1D flow model is established to study energy relaxation. The vibrational and electronic excited modes are critical for the energy transfer. Analysis of energy relaxation is done in a wide range of heights and Mach numbers. The division of thermochemical state in Height-Mach number diagram is obtained.